CAUSES OF HORMONE IMBALANCE IN WOMEN AND MODERN METHODS OF ELIMINATING IT - Xaqqulova Marta Alisherovna; Rahmonova Umida Tohir qiz; Abdumannonova Xidoyatxon Ganisher qizi (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
This article analyzes the main causes of hormonal imbalance in women, methods for identifying clinical signs, and modern treatment approaches. The study incorporates practical experiences from endocrinology, gynecology, and psychology, as well as diagnostic and therapeutic opportunities within the healthcare system of Uzbekistan. It also highlights internal and external factors causing hormonal imbalance in women during pregnancy, reproductive age, and menopause.